Effect of Feeding Counseling and Massage Therapy on HAZ and WAZ Scores in Stunted Toddlers - Qomariyah Qomariyah; Desi Soraya; Ellyzabeth Sukmawati (Jurnal Bidan Cerdas, 2025)
Background: Stunting remains a major nutritional problem influenced by inadequate feeding practices during early childhood. This study examined the effect of feeding counseling and massage therapy for feeding difficulties on the nutritional status of stunted toddlers. Methods: A quasi-experimental design with a non-equivalent control group was conducted among 40 stunted toddlers aged 24–59 months in Semarang City. The intervention group received feeding counseling and massage therapy for three months, while the control group received standard care. Nutritional status was assessed using Weight-for-Age Z-score (WAZ) and Height-for-Age Z-score (HAZ). Results: The intervention led to a significant improvement in HAZ scores (p < 0.001), indicating a positive trend in linear growth, while WAZ scores showed no significant change. Conclussion: These results suggest that feeding counseling combined with massage therapy for feeding difficulties may support linear growth among stunted toddlers. However, the small sample size and short intervention period limit the generalizability of these findings.